Електроенергія з відновлюваних джерел як товар: конкурентні переваги на ринку ЄС - Сіренко, Світлана Олексіївна; Sirenko, Svitlana (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Метою статті є дослідження стану сектора відновлювальної енергетики України та окреслення проблем і перспектив його розвитку в умовах війни. Показано, що сонячна енергетика в Україні демонструє стрімке зростання і активно інтегрується у структуру енергетичної безпеки держави. Розглянуто сучасні тренди розвитку відновлюваної енергетики. Проаналізовано кількість виробників електроенергії з альтернативних джерел за видами генерації та географічний розподіл виробників електроенергії із сонячної генерації. Україна, переважним чином, імпортує сонячні панелі для побудови електростанцій. Проаналізовано динаміку обсягів імпорту сонячних панелей та структуру встановлених потужностей домогосподарствами та енергетичними кооперативами. Окреслено проблеми, які стримують розвиток відновлюваних джерел енергії в Україні. /// EN: The purpose of the article is to study the state of the renewable energy sector in Ukraine and outline the problems and prospects for its development in wartime conditions. Relevance of the topic. The development of renewable energy sources and distributed generation is an element of European integration and a basic condition for energy security. The introduction of energy-efficient technologies and the use of alternative energy sources is taking place at a rapid pace. It is important to assess the potential of renewable energy sources for Ukraine as an anti-crisis response to the challenges of wartime and to consider problems that require understanding and making systemic decisions. In the research process, general scientific methods were used: induction and deduction – to analyze trends and vectors of renewable energy development; cause-and-effect relationships – to predict the prospects for the implementation of renewable energy; analysis and synthesis – for a detailed analysis of individual components, their relationships and identification of the main trends in the development of renewable energy in the world and Ukraine; abstract-logical – to summarize information from scientific sources, form theoretical conclusions; graphic-tabular – to visualize the results of the study. The article shows that solar energy in Ukraine is demonstrating rapid growth and is increasingly integrated into the structure of the state's energy security. Current trends include the active construction of solar power plants for own consumption, the growing popularity of hybrid inverters that combine the functions of generation and storage of energy. The number of producers of electricity from alternative sources by type of generation and the geographical distribution of producers of electricity from solar generation are analyzed. Ukraine mainly imports solar panels for the construction of power plants. The dynamics of the volume of imports of solar panels and the structure of installed capacities by households and energy cooperatives are analyzed. The problems that hinder the development of renewable energy sources in Ukraine are outlined.
Renewable electricity as a commodity: competitive advantages in the EU market
Keywords: відновлювана енергетика; джерела енергії; розподільна генерація; сонячна енергія; вітрова енергія; енергетична безпека; renewable energy; energy sources; distributed generation; solar energy; wind energy; energy security